KOMPARASI PENENTUAN LOKASI PEMASANGAN KAPASITOR ANTARA GI. DUMAI DAN GI. BAGAN SIAPI-API - Hazri, M Wahyudi; Yulisman, Yulisman; Dwiharzandis, Aggrivina (Rang Teknik Journal, 2026)
During peak load conditions, significant voltage drops are observed in the Dumai transmission subsystem. The minimum voltages recorded at the Dumai, Bagan Siapi-api, and Dumai Industrial Area substations are 134.7 kV, 133.0 kV, and 131.1 kV, respectively, exceeding the permissible voltage deviation limits. To mitigate this condition, a shunt capacitor is designed and evaluated through modeling and simulation. Analytical and DigSILENT PowerFactory 2021 simulation results indicate that a 25 MVAR shunt capacitor installed at the Bagan Siapi-api Substation provides the most suitable compensation. The installation increases the bus voltage by 8.10 kV to 141.10 kV, corresponding to a voltage deviation of 5.93% from the nominal value. Furthermore, total system losses in the Riau subsystem are reduced from 20.63 MW and −352.8 MVAR to 19.88 MW and −366.8 MVAR, or reduction 0,75 MW. These results confirm that shunt capacitor integration effectively improves voltage profiles while reducing reactive power flow and system losses.Keywords: shunt capacitor, substation, voltage drop, DIgSILENT PowerFactory 2021, voltage improvement, system losses